2013
DOI: 10.2527/jas.2012-6160
|View full text |Cite
|
Sign up to set email alerts
|

Immune system stimulation increases the optimal dietary methionine to methionine plus cysteine ratio in growing pigs1

Abstract: Chronic subclinical levels of disease occur frequently in intensive swine production and compromise nutrient use efficiency. Feeding additional Met plus Cys (M+C) has been implicated in improving the response of the animal to immune system stimulation (ISS) because they can serve as substrates for generating compounds involved in the immune response, such as glutathione and acute phase proteins. A N-balance study was conducted to assess the optimal dietary Met to Met plus Cys ratio (M:M+C) during ISS in 20-kg … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
32
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 39 publications
5
32
1
Order By: Relevance
“…However, the present study found a decreasing trend of plasma albumin with increasing SID SAA:Lys immediately after infection. These findings are in contradiction with work by Litvak et al (2013) who found that higher Met:SAA increased plasma albumin. Albumin catabolism produces AA and it is thought that the decrease albumin in animals suffering from infection is due to increased breakdown rather than decreased synthesis (Reeds and Jahoor, 2001).…”
Section: Infection With E Coli and Assessment Of Inflammation And Imcontrasting
confidence: 99%
See 1 more Smart Citation
“…However, the present study found a decreasing trend of plasma albumin with increasing SID SAA:Lys immediately after infection. These findings are in contradiction with work by Litvak et al (2013) who found that higher Met:SAA increased plasma albumin. Albumin catabolism produces AA and it is thought that the decrease albumin in animals suffering from infection is due to increased breakdown rather than decreased synthesis (Reeds and Jahoor, 2001).…”
Section: Infection With E Coli and Assessment Of Inflammation And Imcontrasting
confidence: 99%
“…Nevertheless, literature on plasma albumin is contrasting where some authors (Heegaard et al, 2011;Rakhshandeh and de Lange, 2012) showed no response of immune stimulation (using an LPS injection) on plasma albumin, however, Litvak et al (2013) found that immune stimulation caused by LPS injection decreased plasma albumin. Rothschild et al (1979) found that in cases of myxedema there was evidence of tissue trapping of albumin.…”
Section: Infection With E Coli and Assessment Of Inflammation And Immentioning
confidence: 99%
“…injection of LPS was selected as the non-infectious disease model. Based on previous studies, this model shows a predictable response immediately following the initial LPS injection, but pigs can develop tolerance to LPS such that they no longer exhibit a clinical response to subsequent LPS injections (Rakhshandeh and de Lange, 2012;Litvak et al, 2013). This is consistent with the pattern of N retention observed in the preliminary study (Fig.…”
Section: Discussionsupporting
confidence: 88%
“…Because Met is an upstream precursor of Cys through the transsulfuration pathway, it has been suggested that Met plays an important role during the APR (Lu, 2009). In fact, Litvak et al (2013) observed a significant decrease in albumin concentration (38.3 vs 33.7 g/L) in growing pigs fed a Met-deficient diet before and after an APR was induced via intramuscular injection of Escherichia coli LPS. In contrast, albumin remained unchanged in pigs fed adequate amounts of Met before and after APR induction.…”
Section: Biomarkers Of Liver Functionmentioning
confidence: 89%